Live algal sorbents for the removal of potentially toxic elements: a review. Issue 1 (31st December 2023) - Read, Sarah K.; Semião, Andrea J.C.; Graham, Margaret C.; Ross, Michael
ABSTRACT: To increase the sustainability of industrial wastewater treatment, biological sorbents have been explored for the removal of potentially toxic elements (PTEs). Algae are particularly attractive biosorbents due to their high concentration of negatively charged extracellular binding sites. Although there has been significant focus on dried algal sorbents for this reason, live algal sorbents may expand potential binding sites through intracellular accumulation and replenishment of active binding sites through algal growth. A barrier to the application of live algal sorbents in WWT is managing a sorbent's metabolic requirements while achieving maximum PTE removal. Many reviews investigating the performance of live algal sorbents have focused on species-specific differences in PTE removal, without defining how intracellular detoxification mechanisms may be impacted by system conditions. The following review explores the physico-chemical conditions and sorbents qualities that affect the production of an integral intracellular ligand for PTE accumulation, phytochelatins (PCs). This review uniquely highlights how system conditions may support or inhibit the proper functioning of intracellular detoxification mechanisms governed by PCs. Opportunities for optimization and areas requiring further research are also suggested.